Green Synthesis Characterization and Antimicrobial Activity Evaluation of Manganese Oxide Nanoparticles and Comparative Studies with Salicylalchitosan Functionalized Nanoform - Haneefa, M. Muhamed (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: In this study, we have demonstrated the synthesis of manganese metal oxide nanoparticles (NPs) by a green synthesis manner using lemon extract as a reducing agent and turmeric curcumin extract as capping agent. The as-synthesized nanomaterials were biofunctionalized with salicylalchitosan which was obtained from the source of chitosan to enhance the antimicrobial activity of those materials. Materials and Methods: The synthesized materials were characterized using ultraviolet-visible and Fourier transform infrared spectroscopic techniques. Scanning electron microscopy and transmission electron microscopy analysis were employed to evaluate the morphological and structural properties of the both synthesized nanoforms. Furthermore, the effect of antibacterial and antifungal activity of those materials was analyzed using some standard Gram-positive and Gram-negative bacteria and funguses. Results: The morphological studies represented that both non-functionalized and biofunctionalized manganese oxide NPs (MONPs) formed are of spherical morphology but exhibited with difference in size about 50 nm and 40-60 nm, respectively. The performance of antimicrobial activity of biofunctionalized MONPs was exhibited better than the non-functionalized NPs. Conclusion: The results are revealed that the biofunctionalized MONPs showed higher antibacterial and antifungal activities, and our findings from this work have been provided the new way in the potential application of MONPs through a biofunctionalization process in the clinical and drug invention field.